10 - Internet and the Egyptian Public Sphere: https://doi.org/10.4314/ad.v35i4.70223 - Mehanna, Omnia (Africa Development, 2021)
The Internet offers many actors in the society ways to present and raise discussion of ideas that is not possible or easy to engage in, especially in societies with conservative facades such as the Egyptian society. The number of Internet users in Egypt had reached 8.6 million by March 2008. This means that more than 10.per cent of the total Egyptian population had access to the Internet. The number of Internet users in Egypt is the third highest in Africa and represents about 17 per cent of the total number of users in Africa. By taking advantage of the opportunity of having greater access to the Internet and using the security of being anonymous, if one desired, provided by this medium of communication, increasing numbers of Egyptians started using the Internet to gain information and engage in political, social and religious discussions. This new E-public sphere in Egypt is not completely virtual, nor is it completely real. The Internet facilitated more chances to networking, forming alliances and addressing the public. This has led to the emergence of a kind of alternative media run by professionals, semi-professionals and amateurs. And of equal importance, an increasing number of blogs and websites started addressing highly controversial social and religious issues. This article, focusing on websites and blogs, explores the new trends which the Internet gave rise to, as well as institutions – such as government and established religious institutions – whose power to monopolise public debates has been challenged by the Internet in Egypt, till 2008. The paper also shows how the state interacts with these trends through recent attempts to increase censorship of the Internet, and in particular its usage for political mobilisation.